Status, Threats, and Conservation of the Mega-Reptilian Fauna of Southern Assam, India - Singha, Utsab; Choudhury, Amir Sohail; Chakravarty, Himabrata; Mazumder, Muhammed Khairujjaman; Barbhuiya, Salem Ahmed (Journal of the Bombay Natural History Society (JBNHS), 2020)
Growing human population, demand for agricultural land, rapid urbanization, and industrialization have resulted in deforestation, climate change, and pollution, which are among the important factors leading to extirpation and extinction of wildlife in recent years, compounded by poaching, human-wildlife conflicts and retaliation, and medicinal and ethnic uses of wildlife. According to IUCN (Uetz et al. 2019), at least 32 species and 6 subspecies of reptiles have gone extinct in recent decades. Local extirpation of reptiles is quite high in different parts of the globe, especially in populated countries with high anthropogenic pressures. Southern Assam (India) has been home to a large number of reptiles. The species inventory includes mega-reptilian fauna like Mugger, Gharial, Common Water Monitor, Bengal Monitor, and Yellow Monitor. Unfortunately, Gharial and Mugger have been extirpated from the region, and the rest may follow. The present article details the status, distribution, and threats faced by these reptiles in the region, and proposes conservation recommendations. While the article is largely based on review of literature, we have included observations from our field studies to substantiate the content.